Counseling services and their relationship to self-confidence among secondary school students in Taif Governorate - Al-Harthi, Hussain Ahmad (Journal of Educational and Psychological Sciences, 2020)
The study aimed to find the relationship between counseling services and self-confidence among high school students in Taif Governorate. To achieve the goal of the research, the researcher used the descriptive approach. A random sample of secondary school students in Taif Governorate was selected, amounting to 750 students, and it represents about 5% of the total study population, which numbered about 15000 students. The study tools were the scale of indicative services prepared by the researcher. And a measure of self-confidence prepared by Al-Qawasmeh and Al-Farah (1996).The study found that there is a positive correlation between counseling services provided to secondary school students in Taif Governorate and self-confidence, and the correlation coefficient has reached (0.77). In light of the results of the study, the researcher recommended a number of recommendations, Preparing counseling programs by the Department of Student Guidance and Guidance in the Department of Education and applying them in schools to develop self-confidence., Providing the necessary training courses for student counselors to provide counseling services more effectively., Designing special counseling programs by specialists in the Department of Student Guidance and Guidance in the Department of Education and Universities for students who suffer from low self-confidence- Spreading cultural awareness in the family about the nature of adolescence as a development stage, while clarifying its characteristics and manifestations.
Keywords: self-confidence; counseling services; student counseling